2004
DOI: 10.1023/b:pham.0000012153.71993.cb
|View full text |Cite
|
Sign up to set email alerts
|

Expression Levels of Renal Organic Anion Transporters (OATs) and Their Correlation with Anionic Drug Excretion in Patients with Renal Diseases

Abstract: These results suggest that hOAT3 plays an important role for anionic drug secretion in patients with renal diseases and that the expression levels of drug transporters may be related to the alteration of renal drug secretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
77
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 98 publications
(81 citation statements)
references
References 27 publications
2
77
0
1
Order By: Relevance
“…One of the first post-OAT-cloning studies evaluating OAT regulation by renal disease reported that patients with several forms of renal disease, when assessed as a group, exhibited reduced renal cortical hOAT1 mRNA levels [114]. In addition, although hOAT3 mRNA levels were unaltered in patients with renal disease, elimination of the b-lactam antibiotic cefazolin exhibited a significant correlation with renal hOAT3 mRNA levels.…”
Section: Phosphorylationmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the first post-OAT-cloning studies evaluating OAT regulation by renal disease reported that patients with several forms of renal disease, when assessed as a group, exhibited reduced renal cortical hOAT1 mRNA levels [114]. In addition, although hOAT3 mRNA levels were unaltered in patients with renal disease, elimination of the b-lactam antibiotic cefazolin exhibited a significant correlation with renal hOAT3 mRNA levels.…”
Section: Phosphorylationmentioning
confidence: 99%
“…In addition, although hOAT3 mRNA levels were unaltered in patients with renal disease, elimination of the b-lactam antibiotic cefazolin exhibited a significant correlation with renal hOAT3 mRNA levels. Cefazolin was confirmed as a substrate for hOAT3 in HEK293 cells [114]. Further studies examined the effect of bilateral ureteral obstruction (BUO) in rats [115].…”
Section: Phosphorylationmentioning
confidence: 99%
“…The mRNA expression levels of OCT2 and OAT1-4 were quantified as described previously (Motohashi et al 2002;Sakurai et al 2004). Briefly, total RNA was isolated from specimens using a MagNA Pure LC RNA isolation Kit II (Roche Diagnostic GmbH, Mannheim, Germany) and was reverse transcribed to yield complementary DNA (cDNA).…”
Section: Quantification Of Oct2 and Oat1-4 Mrna Expressionmentioning
confidence: 99%
“…It has been demonstrated that variations in the expression levels of SLC22A are responsible for the individual variations in pharmacokinetics by clinical studies (Sakurai et al 2004(Sakurai et al , 2005 and in vivo animal experiments (Ji et al 2002;Deguchi et al 2005). For example, we previously reported that the messenger ribonucleic acid (mRNA) level of OAT3 among OAT1-4 significantly correlated with the elimination rates of cefazolin and phenolsulfonphthalein in patients with renal diseases (Sakurai et al 2004(Sakurai et al , 2005.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation